Expression and purification of soluble and stable ectodomain of natural killer cell receptor LLT1 through high-density transfection of suspension adapted HEK293S GnTI(-) cells - Bláha, Jan; Pachl, Petr; Novák, Petr; Vaněk, Ondřej (Protein expression and purification, 2015)
Lectin-like transcript 1 (LLT1, gene clec2d) was identified to be a ligand for the single human NKR-P1 receptor present on NK and NK-T lymphocytes. Naturally, LLT1 is expressed on the surface of NK cells, stimulating IFN-γ production, and is up-regulated upon activation of other immune cells, e.g. TLR-stimulated dendritic cells and B cells or T cell receptor-activated T cells. While in normal tissues LLT1:NKR-P1 interaction (representing an alternative "missing-self" recognition system) play an immunomodulatory role in regulation of crosstalk between NK and antigen presenting cells, LLT1 is upregulated in glioblastoma cells, one of the most lethal tumors, where it acts as a mediator of immune escape of glioma cells. Here we report transient expression and characterization of soluble His176Cys mutant of LLT1 ectodomain in an eukaryotic expression system of human suspension-adapted HEK293S GnTI(-) cell line with uniform N-glycans. The His176Cys mutation is critical for C-type lectin-like domain stability, leading to the reconstruction of third canonical disulfide bridge in LLT1, as shown by mass spectrometry. Purified soluble LLT1 is homogeneous, deglycosylatable and forms a non-covalent homodimer whose dimerization is not dependent on presence of its N-glycans. As a part of production of soluble LLT1, we have adapted HEK293S GnTI(-) cell line to growth in suspension in media facilitating transient transfection and optimized novel high cell density transfection protocol, greatly enhancing protein yields. This transfection protocol is generally applicable for protein production within this cell line, especially for protein crystallography.
Keywords: transfekce; roztoky; Protein Stability; Polyethyleneimine; Protein Folding; multimerizace proteinu; stabilita proteinů; HEK293 buňky; krystalizace; Protein Structure, Tertiary; Transfection; terciární struktura proteinů; molekulární sekvence - údaje; Amino Acid Sequence; HEK293 Cells; Disulfides; sbalování proteinů; polyethylenimin; rozpustnost; polysacharidy; lektiny typu C; Solutions; lidé; Crystallization; Lectins, C-Type; N-Acetylglucosaminyltransferases; Humans; buňky NK; sekvence aminokyselin; DNA; Molecular Sequence Data; Polysaccharides; disulfidy; glykosylace; Killer Cells, Natural; N-acetylglukosaminyltransferasy; Glycosylation; Solubility; Protein Multimerization